Globalization, culture and development the UNESCO Convention on cultural diversity - De Beukelaer, Christiaan 1986-; Pyykkonen, Miikka; Singh, J. P. 1961- (Palgrave Macmillan, 2015)
"The 2005 UNESCO Convention on the Protection and Promotion of the Diversity of Cultural Expressions provides an international policy lens for analysing broad debates on issues of cultural globalization and development. The interdisciplinary contributions in this volume offer a fresh understanding of these key issues whilst examining cultural globalization, which is conceived in terms of artistic expressions and entertainment industries and interpreted anthropologically as the rituals, symbols, and practices of everyday life. The broad gamut of theories, methods, and evidence collected by the editors outlines UNESCO's accomplishments, shortcomings, and future policy prospects. This edited collection has a clear message: The Convention is a useful and important instrument in the debate on cultural diversity, but not broad enough or sufficient to confront major challenges concerning human rights, sustainability, and cultural diversity as a whole."